Fundamentals of ophthalmic dispensing 18: Law and regulation – part 1. Issue 6 (June 2021) - Black, Tina Arbon; Black, Peter
Abstract : The sale of optical appliances is governed partly by ordinary consumer legislation and specifically through the Opticians Act and the various orders of the General Optical Council. Here Tina Arbon Black and Peter Black take a look at the legislation, regulations and standards that apply to ophthalmic dispensing.